Att bli sig själv: En kvalitativ studie om psykoterapeuters syn på människans autenticitet - Lagerquist,Axel (2025)
Authenticity is a concept that since a long time has been of relevance within philosophy and later also psychology. It constitutes an ideal in our time and is associated with psychological health. At the same time, there is disagreement within the research field of psychology about how the concept should be understood and conceptualized. This qualitative study aimed to increase the understanding of authenticity, more specifically what it means to live authentically, how authenticity relates to socially non-desirable sides and what implications it has on the way of life, and what opportunities and obstacles there are for living a more authentic life. Semi-structured interviews were carried out with eight licensed psychologists with psychotherapist licenses whereupon a thematic analysis was made that resulted in six themes. It appears that the authentic life is associated with being able to balance one’s focus between the self and others, having a free inner life, and courage. To be authentic in relation to socially non-desirable sides mean to make conscious decisions where the outer action can constitute a compromise. Introspection and safety, where especially the relational aspect is apparent, enable authenticity. Defenses are regarded as obstructive. The participants’ view on authenticity has several similarities with Kernis and Goldman’s (2006) conceptualization and capacity for mentalization. Other related concepts are attachment, agency, and defenses.
Keywords: autenticitet; humanistisk psykologi; existentialism; mental hälsa; mentalisering; authenticity; humanistic psychology; mental health; mentalization